Weighted Szeged indices of some graph operations - Kannan Pattabiraman (Transactions on Combinatorics, 2016)
In this paper, the weighted Szeged indices of Cartesian product and Corona product of twoconnected graphs are obtained. Using the results obtained here, the weighted Szeged indices ofthe hypercube of dimension n, Hamming graph, C4 nanotubes, nanotorus, grid, t− fold bristled,sunlet, fan, wheel, bottleneck graphs and some classes of bridge graphs are computed.